Response to "What do Klein et al. tell us about test scores in Texas?" - Stephen P. Klein; Laura S. Hamilton; Daniel F. McCaffrey; Brian M. Stecher (Arizona State University, 2005)
Wherein the authors reply to Toenjes, Vol. 13 No. 36 "What do Klein et al. tell us about test scores in Texas?"